ANALISIS KEPUTUSAN BELANJA ONLINE TERHADAP PERILAKU KONSUMTIF MAHASISWA DALAM PERSPEKTIF EKONOMI ISLAM (Studi Kasus Mahasiswa Fakultas Ekonomi Universitas Almuslim) - Saryulis, Saryulis; Musrizal, Musrizal; Mukhlis, Mukhlis; Yanna, Sri (IndOmera, 2023)
This study aims to analyze the relationship between purchasing decision variables and consumptive behavior of students at the Faculty of Economics, Almuslim University. Decision Variables have several instruments in the form of product, price, service and risk. And what is the Islamic view of the consumptive behavior of Almuslim University Faculty of Economics students in shopping online. The type of research used in this research is quantitative research. In this study the population was students of the Faculty of Economics, Almuslim University by taking a sample of 45 people as respondents. The data collection technique is through a questionnaire with a Likert scale that guarantees its validity and reliability. The statistical tool used is through multiple linear regression. The results of the study found a) there were only two significant variables, namely online purchasing decisions and product factors that had a positive relationship to consumptive behavior, b) From an Islamic perspective, student consumptive behavior leads to excessive behavior caused by frequent online shopping just because of the desire to support appearance not as needed, and when shopping online just follow the trend.